Exploring Positional and Age Variations in Hamstring Eccentric Strength in Academy Football Players - ALTUNDAĞ , Emre; SOYLU , Çağlar; AKYILDIZ , Zeki (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2024)
This study investigates the positional differences in hamstring eccentric strength among academy football players and its implications for performance and injury prevention. A cross-sectional design was employed, involving 125 male players aged 12-17 from a football academy in Turkey. Participants were categorized into six positional groups: forwards, midfielders, center-backs, full-backs, wingers, and goalkeepers. Eccentric hamstring strength was assessed using the iVMES H-BORD® device during Nordic hamstring exercises. The results indicated no statistically significant differences in hamstring eccentric strength across positions, though trends suggested that wingers and strikers exhibited higher maximal eccentric strength than defenders and goalkeepers. Additionally, older players (15-17 years) showed significantly higher hamstring strength than younger players (12-14 years), highlighting the importance of maturation and targeted strength training. While the findings emphasize the need for position-specific conditioning programs, the study’s limitations include a small sample size and cross-sectional design. Further longitudinal research is recommended to explore the long-term effects of eccentric training and positional demands in youth football development. These results provide valuable insights for coaches and sports scientists to optimize injury prevention and performance enhancement in academy football.